Ad hoc Taxonomies: A Baltic Parallel to the Scandinavian Absolute Positives - Holvoet, Axel; Spraunienė, Birutė (Scandinavistica Vilnensis, 2014)
The article deals with the extension of definite markers into the domain of indefinite NPs in Scandinavian and Baltic. Definite articles evolving further down the grammaticalization path typically become markers of specificity (Greenberg 1978, Himmelmann 1998), but the development of definite markers in Baltic and Scandinavian languages (formally divergent as Baltic uses definite adjectives as the principal grammatical means of marking definiteness whereas Scandinavian employs definite articles for this purpose) has taken a different direction. After a brief discussion of the different types of extension of definite markers beyond their core domain in Baltic and Scandinavian, we focus on a specific construction in Scandinavian, the so-called ‘absolute positives’. We suggest that this construction is parallelled by certain Latvian constructions with definite adjectives, the effect being, in both cases, that of evoking ad hoc taxonomies. Finally, we present some considerations on the possible origin of the constructions discussed.
Keywords: definite adjectives; definiteness; definiteness mismatch; absolute positives; ad hoc categories